Endobronchial carcinoid tumor: Radiological findings of a clinical case - Queiroz,Rodolfo Mendes (2018)
Summary We describe the case of a female patient, 21 years old, complaining of dyspnea attacks and wheezing 2 years ago. Chest radiography showed volume loss in the left lower lobe and ipsilateral retrocardiac triangular basal opacity. CT scan showed an extensive solid mass with apex protruding into the left main and lower lobar bronchi, causing distal atelectasis. Histopathological and immunohistochemical study of transbronchial biopsy of the lesion revealed a typical carcinoid tumor, confirmed after tumor resection with total left pneumectomy.